You need to first make everything positive:
x^2=36
Then you need to get the square root of each side:
x=6 or -6
Hope this helps :)
Answer:
k=10
Step-by-step explanation:
g(x)=2x^2+ kx+18
when x=-2
g(-2)=2 (-2)^2 -2k +18
Since when x is -2, y =6
6=2 (-2)^2 -2k +18
6=18+8-2k
2k=26-6
2k=20
k=10
Answer:
Discount= $4.94
Final Price= $28.04
Step-by-step explanation:
Discount = original price x discount / 100
Discount= 32.99 x 15/ 100
Discount= 494.85/ 100
You save= $4.9485 ($494)
Final Price= original price - discount
Final Price= 32.99 - 4.9485
Final Price= $28.04
Answer:
<h2>(2x - 3y)(4x - y) = 8x² - 14xy + 3y²</h2>
Step-by-step explanation:
Use FOIL: <em>(a + b)(c + d) = ac + ad + bc + bd</em>
(2x - 3y)(4x - y) = (2x)(4x) + (2x)(-y) + (-3y)(4x) + (-3y)(-y)
= 8x² - 2xy - 12xy + 3y²
<em>combine like terms</em>
= 8x² + (-2xy - 12xy) + 3y² = 8x² - 14xy + 3y²
Answer:
-38.8
Step-by-step explanation:
uh just do verticle subtraction or use a calculator